Branched-chain amino acids promotes the repair of exercise-induced muscle damage via enhancing macrophage polarization - Dong, Yunfeng; Zhang, Xuejiao; Miao, Rui; Cao, Wei; Wei, Hao; Jiang, Wei; Gao, Ruirui; Yang, Yanhui; Sun, Haipeng; Qiu, Junqiang (Frontiers in Physiology, 2022)
The repair of exercise-induced muscle damage (EIMD) is closely related with inflammation. Branched-chain amino acids (BCAAs), as a nutritional supplement, promote EIMD repair; however, the underlying mechanism remains unclear. In vivo, Sprague–Dawley rats were subjected to Armstrong’s eccentric exercise (a 120-min downhill run with a slope of −16° and a speed of 16 m·min−1) to induce EIMD and BCAA supplement was administered by oral gavage. Protein expression of macrophages (CD68 and CD163) and myogenic regulatory factors (MYOD and MYOG) in gastrocnemius was analyzed. Inflammatory cytokines and creatine kinase (CK) levels in serum was also measured. In vitro, peritoneal macrophages from mice were incubated with lipopolysaccharide (LPS) or IL-4 with or without BCAAs in culture medium. For co-culture experiment, C2C12 cells were cultured with the conditioned medium from macrophages prestimulated with LPS or IL-4 in the presence or absence of BCAAs. The current study indicated BCAA supplementation enhanced the M1/M2 polarization of macrophages in skeletal muscle during EIMD repair, and BCAAs promoted M1 polarization through enhancing mTORC1-HIF1α-glycolysis pathway, and promoted M2 polarization independently of mTORC1. In addition, BCAA-promoted M1 macrophages further stimulated the proliferation of muscle satellite cells, whereas BCAA-promoted M2 macrophages stimulated their differentiation. Together, these results show macrophages mediate the BCAAs’ beneficial impacts on EIMD repair via stimulating the proliferation and differentiation of muscle satellite cells, shedding light on the critical role of inflammation in EIMD repair and the potential nutritional strategies to ameliorate muscle damage.